2019
DOI: 10.3136/fstr.25.449
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Components from Wasabi (<i>Wasabia japonica</i> Matsumura) Flowers and Investigation of Their Antioxidant and Anti-inflammatory Activities

Abstract: Wasabi (Wasabia japonica Matsumura) is a perennial plant, and its rhizome is widely used as a pungent spice. Wasabi rhizome has been reported to have various physiological activities, but the flower has not been studied in depth. The aim of the present study was to isolate compounds from wasabi flowers and clarify their antioxidant and anti-inflammatory activities. Three phenylpropanoids, one alkaloid and seven flavonoids were isolated from wasabi flowers. Among them, 2"-O-trans sinapoyl isovitexin was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Therefore, our results were in good agreement with previous investigations on the identification of isosaponarin and ferulic acid in the leaves [11,20], isorhamnetin-3-glucoside and astragalin in the flowers [10], and trans-ferulic acid, as well as trans-pcoumaric acid, in the roots [27] of E. japonicum. To the best of our knowledge, the other phenolic acids and flavonoids were identified for the first time in the investigated species.…”
Section: Phytochemical Analysissupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, our results were in good agreement with previous investigations on the identification of isosaponarin and ferulic acid in the leaves [11,20], isorhamnetin-3-glucoside and astragalin in the flowers [10], and trans-ferulic acid, as well as trans-pcoumaric acid, in the roots [27] of E. japonicum. To the best of our knowledge, the other phenolic acids and flavonoids were identified for the first time in the investigated species.…”
Section: Phytochemical Analysissupporting
confidence: 93%
“…Ferulic acid, luteolin, isoorientin, and rutin showed a significant inhibitory activity. Importantly, luteolin (IC 50 = 4.09 ± 0.28 µg/mL) and isoorientin (IC 50 = 6.73 ± 0.45 µg/mL) showed a stronger activity compared to Trolox (IC 50 = 6.48 ± 0.73 µg/mL) [10].…”
Section: Antioxidant Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…Wasabi ( Wasabia japonica ), a perennial plant that is native to Japan and belongs to the Brassicaceae family, is commonly used in food as a pungent spice [ 11 ]. Wasabi has numerous health-promoting effects, such as antioxidant, anti-inflammatory, anti-obesity, anti-cancer, antiviral, and neuroprotective activities [ 12 , 13 , 14 , 15 , 16 ]. Previous studies have shown that wasabi leaves contain flavonoids [ 11 ], phenylpropanoids [ 17 ], terpenoids [ 18 ], and carotenoids [ 18 ].…”
Section: Introductionmentioning
confidence: 99%